Influence of race/ethnicity on response to lupus nephritis treatment: the ALMS study - Isenberg, David (Oxford University Press, 2010)
Objective. To compare the efficacy and safety of mycophenolate mofetil (MMF) and intravenous cyclophosphamide (IVC) as induction treatment for lupus nephritis (LN), by race, ethnicity and geographical region. Methods. A total of 370 patients with active Class III–V LN received MMF (target dose 3.0 g/day) or IVC (0.5–1.0 g/m(2)/month), plus tapered prednisone, for 24 weeks. Renal function, global disease activity, immunological complement (C3 and C4) and anti-dsDNA levels are the outcomes that were assessed in this study. Results. MMF was not superior to IVC as induction treatment (primary objective). There were important pre-specified interactions between treatment and race (P = 0.047) and treatment and region (P = 0.069) (primary endpoint). MMF and IVC response rates were similar for Asians (53.2 vs 63.9%; P = 0.24) and Whites (56.0 vs 54.2%; P = 0.83), but differed in the combined Other and Black group (60.4 vs 38.5%; P = 0.03). Fewer patients in the Black (40 vs 53.9%; P = 0.39) and Hispanic (38.8 vs 60.9%; P = 0.011) groups responded to IVC. Latin American patients had lower response to IVC (32 vs 60.7%; P = 0.003). Baseline disease characteristics were not predictive of response. The incidence of adverse events (AEs) was similar across groups. Serious AEs were slightly more prevalent among Asians. Conclusions. MMF and IVC have similar efficacy overall to short-term induction therapy for LN. However, race, ethnicity and geographical region may affect treatment response; more Black and Hispanic patients responded to MMF than IVC. As these factors are inter-related, it is difficult to draw firm conclusions about their importance. Trial registration. National Institutes of Health, www.clinicaltrials.gov, registration number NCT00377637.